Microbiological quality and characteristics of probiotic products in China. (4th July 2013) - Chen, Tingtao; Wu, Qinglong; Li, Shengjie; Xiong, Shunqiang; Jiang, Shuying; Tan, Qianglai; Zhang, Zhichao; Zhu, Daochen; Wei, Hua
Abstract: BACKGROUND: Probiotics are widely used in the food industry and medicine fields in China, but few studies have been conducted to evaluate the actual microbial amounts and species in probiotic products, which may conflict with the labels and mislead consumers to choose inappropriate foods or medicines . RESULTS: Twenty commercial dairy products and eight commercial 'healthcare' samples were collected from markets in China and tested using culture‐dependent and culture‐independent methods. The results suggested that the total bacterial counts of most commercial products met the minimum quantitative requirement of the Chinese national standard (6.00 log colony‐forming units g −1 ). However, the bacterial counts of specific species were inconsistent with the labelling. In parallel, denaturing gradient gel electrophoresis analysis indicated that some probiotic‐containing products were wrongly labelled; no Bifidobacterium species were detected in the products claiming to contain bifidobacteria, and the probiotic characteristics (antimicrobial activity, acid resistance and bile resistance) of some isolates had degraded. Moreover, some contaminating bacteria, e.g. Enterobacter sp., Klebsiella sp. and Serratia sp., were also detected in these products . CONCLUSION: The combination of culture‐dependent and culture‐independent methods was proven to quickly and conveniently detect the microbial diversity in probiotic products, and more effort is required to regulate the probiotic market in China. © 2013 Society of Chemical Industry